Corporate finance - Ross, Stephen A. (New York, NY McGraw Hill LLC, 2022)
"The teaching and the practice of corporate finance are more challenging and exciting than ever before. Among other things, the first two decades of the twenty-first century brought us the global financial crisis of 2008-2009 and the COVID-19 pandemic of 2020-2021. Both shocks led to major corporate restructurings, and we still routinely see announcements in the financial press about takeovers, junk bonds, financial restructuring, initial public offerings, bankruptcies, and derivatives. In addition, there are the new recognitions of "real" options, private equity and venture capital, subprime mortgages, bailouts, and credit spreads. As we have learned, the world's financial markets are more integrated than ever before. Both the theory and practice of corporate finance have been moving ahead with uncommon speed, and our teaching must keep pace"--
Includes bibliographical references and index.
Keywords: Corporations -- Finance